A QUALITATIVE ANALYSIS OF FORMALIN ON TOfu CIRCULATED IN KUPU VILLAGE MARKET, BREBES CITY - Yuniarti Dewi Rahmawati (Politeknik Negeri Sriwijaya, 2022)
Tofu has a high protein content and water content reaches 85% so that tofu does not last long. One way to prevent damage to foodstuffs is to add preservatives. Formalin is a preservative that is sometimes misused as a preservative in foodstuffs. The research that has been conducted aims to determine the presence or absence of formalin in tofu sold at the Pasar Desa Kupu. The type of research used is descriptive research. Five samples of tofu obtained from traders at Pasar Desa Kupu were then analyzed using a qualitative method using a color reaction. All samples showed positive results with the loss of KMnO4 color and became clear. The same results were shown by the dragon fruit peel kit method.